Analisis Hukum Pidana terhadap Tindak Kekerasan Seksual terhadap Perempuan di Provinsi Banten Berdasarkan UU Nomor 12 Tahun 2022: ANALISIS HUKUM PIDANA TERHADAP TINDAK KEKERASAN SEKSUAL TERHADAP PEREMPUAN DI PROVINSI BANTEN - Sigit Kamseno; Saifun Nufus; Wahyudi Wahyudi (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze the implementation of Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence (UU TPKS) in handling sexual violence against women in Banten Province. The research method used is empirical juridical through the study of legislation, case data and law enforcement practices. The results show that the implementation of the TPKS Law has provided a more comprehensive legal basis for victim protection, but obstacles remain in the aspects of legal structure, legal substance and legal culture. Strengthening the capacity of officials, harmonizing regulations and increasing public awareness are needed to realize effective legal protection for female victims of sexual violence.